The determinants of employee turnover: factors influencing employees intention to leave among expatriate in Scope International (M) Sdn Bhd / Asrulsani Muhammad Rais - Muhammad Rais, Asrulsani (Faculty of Business and Management, 2010)
This research is conduct to carry out “THE DETERMINANTS OF EMPLOYEE TURNOVER: FACTORS INFLUENCING EMPLOYEES INTENTION TO LEAVE AMONG EXPATRIATE IN SCOPE INTERNATIONAL (M) SDN BHD”. Scope International is the Standard Chartered Group’s Global Technology & Operations Hub. A wholly owned subsidiary of Standard Chartered Bank, United Kingdom, SCOPE International is the first Global Shared Services Centre of an international bank in Malaysia. The main objective is to measure and identify the most factors that influence expatriates intention to leave in SCOPE International (M) Bhd. And it consists of four factors that are working environment, pay scale, advancement opportunity, and job satisfaction. There are several problem where employees turnover among expatriate are increasing and this research to study most factor influencing employees among expatriate intention to leave SCOPE International (M) Sdn Bhd. SCOPE International has large number of employees, there surely is a variety of behavior among employees especially from expatriates from India and Singapore. The data and analyzed Statistical Packages analyzed all data collected through the question systematically for Social Science (SPSS). The conclusion for this study was the outcome from the data analysis and findings. Through the research, it shows based on correlation and descriptive Statistic, a clear finding and result observed.